Duterte's disciplinary quarantine how a moral dichotomy was constructed and undermined - Kusaka, Wataru (Philippine studies : historical and ethnographic viewpoints)
"This article explores the characteristics of what I call Duterte's "disciplinary quarantine," which is premised on a moral dichotomy between "good citizens," who abide by strict regulations, and undisciplined "evil others" (pasaway), who endanger the nation. Based on my family's participant observation in Bohol, this article also describes how Boholanos have undermined the moral dichotomy by embracing minor violations to endure the government's protracted and rigid quarantine rules. I suggest that ideas about appropriate behaviors created through people's mutuality and everyday trials and errors are more reliable than top-down "discipline" for a continual struggle against the pandemic. "